The mRNA m(6)A reader YTHDF2 suppresses proinflammatory pathways and sustains hematopoietic stem cell function - Mapperley, Christopher (J Exp Med, 2020)
The mRNA N(6)-methyladenosine (m(6)A) modification has emerged as an essential regulator of normal and malignant hematopoiesis. Inactivation of the m(6)A mRNA reader YTHDF2, which recognizes m(6)A-modified transcripts to promote m(6)A-mRNA degradation, results in hematopoietic stem cell (HSC) expansion and compromises acute myeloid leukemia. Here we investigate the long-term impact of YTHDF2 deletion on HSC maintenance and multilineage hematopoiesis. We demonstrate that Ythdf2-deficient HSCs from young mice fail upon serial transplantation, display increased abundance of multiple m(6)A-modified inflammation-related transcripts, and chronically activate proinflammatory pathways. Consistent with the detrimental consequences of chronic activation of inflammatory pathways in HSCs, hematopoiesis-specific Ythdf2 deficiency results in a progressive myeloid bias, loss of lymphoid potential, HSC expansion, and failure of aged Ythdf2-deficient HSCs to reconstitute multilineage hematopoiesis. Experimentally induced inflammation increases YTHDF2 expression, and YTHDF2 is required to protect HSCs from this insult. Thus, our study positions YTHDF2 as a repressor of inflammatory pathways in HSCs and highlights the significance of m(6)A in long-term HSC maintenance.